G133(P) Improving Professional Practice After Unexpected Infant Death. (7th April 2014) - Garstang, JJ; Griffiths, FE; Sidebotham, P
Abstract : Aims: Since 2008, in England, all unexpected infant deaths must be investigated jointly by police, health and social services. This study aims to learn of bereaved parents' experiences of this joint agency approach (JAA) and use this knowledge to improve professional practice. Methods: Bereaved parents, whose unexpected infants' deaths were investigated by a JAA were eligible to participate in the study. Case records from all agencies were analysed and parents were invited to complete questionnaires or have in-depth interviews. Data were analysed using a Framework Approach. Results: There were 101 eligible families of whom 23 were recruited, 16 families had in-depth interviews, 5 completed questionnaires and 2 allowed case note access only. The median time between infants' deaths and interview or questionnaire completion was 33 weeks; all interviews took place between 2011–3. Most families had mixed experiences of the JAA. In many cases uniformed police arrived at the home along with the ambulance; these police officers' actions were often distressing. Parents were not allowed to go back into their homes to collect possessions; other relatives were required to leave the property immediately. Occasionally police separated parents from their baby. Nearly all families thought that they had been well cared for during their time at the Emergency Department. Most parents found the joint home visit by police and paediatrician to be a helpful experience; however for a few mothers it was deeply distressing to have to return home so soon after the death or talk further with professionals about events. Parents' experiences of follow-up after the death varied; most welcomed the explanations as to why their baby died but complained of months waiting with no information or support. Some parents wanted help accessing emotional support, feeling unable to do this themselves. Conclusion: Parents find the involvement of paediatricians in the JAA helpful; however there is scope for improvements in the way police and health staff respond. Paediatricians should ensure that parents are kept updated with the progress of the investigations. Some parents require more emotional support and professionals should assist them in accessing this.